BIOINFORMATICS AND MOLECULAR ANALYSES IDENTIFIED THE CONTROL REGION AS THE MOST POWERFUL MITOGENOMIC MARKER FOR DISTINGUISHING THE MAIN MATERNAL HAPLOGROUPS IN GOATS - Mustafa, Sarbast I. (Science Journal of University of Zakho, 2024)
Identification of genetic markers to distinguish animals within and between species demands extensive genomic and bioinformatics investigation. Previous studies have not carefully taken into consideration the effect of mitogenomic components on the genetic differentiation of the maternal lineages in goats. As a precaution, the complete goat mitogenome was downloaded from the NCBI database and used in the current study to assess the effects of the choice of mitogenomic fragments on phylogenetic studies and to identify any potential polymorphic region by which the main maternal haplogroups of goats can be classified. Phylogenetic results confirmed that all 13 individual mitochondrial protein-coding genes and 2 ribosomal genes are not applicable to differentiate the maternal lineages. Instead, a single novel polymorphic region with a length of 756 bp within the control region was successfully amplified by newly designed primers. Both phylogenetic analysis and principal components analysis of the sequenced mitogenomic region of the mtDNA control region efficiently differentiated the main maternal haplogroups in goats. Higher numbers of polymorphic sites were found in the control region and the mitogenomic marker region. Highly significant correlations were discovered between the polymorphic sites and the length of each individual mitogenomic component. Our results demonstrate useful guidance and cautionary notes for researchers who are interested in the investigation of genetic diversity in animal species using mtDNA sequences. The bioinformatics and molecular methods used herein can be powerful in selecting a minimum amount of data using PCR amplification when the entire sequences of the mitogenome are unavailable.